The Conceptual Framework of International Law in the Historical Establishment of Islamic Law - Iffan, Ahmad; Mujtahidin, Syamsul; Algifari, Muhammad Faiz (Media Syari'ah : Wahana Kajian Hukum Islam dan Pranata Sosial, 2023)
The legal enactment in the Makkah phase which lasted for approximately 13 years focused on cultivating the faith, strengthening its roots, and maintaining its purity. Islam makes the two sentences of the shahada as the realization of the aqidah as the door to a person's entry into the embrace of Islam which then applies Islamic laws to him. In efforts to adhere to the Islamic creed, it relies on logical arguments. The way to do this is by inviting humans to think about the universe, observing the signs of Allah's power and the beauty of His creation, and thinking about how all of this creation works in an orderly pattern. According to Sheikh Manna, the letters and verses that were included in the Makkah phase describe the orientation of faith by inviting humans to think and see the universe along with the heavens and the earth, witnessing the secrets that Allah keeps behind it all, and accuracy and perfection. in the universe itself, which is neatly arranged without any defects or doubts in it. Determination of Medina Law, The hijrah event was a separation between two societies in Islamic history. While in Mecca, the Islamic faith had been firmly ingrained in the souls of the Muhajirin and, like the Ansar, had taken the oath of allegiance. It was there that the seeds began to form which became the embryo of the founding of an Islamic society. Then they made Medina a place to settle in order to develop these seeds. "It is at this stage that da'wah begins to enter the stage of implementation in an organized manner," he said. Sheikh Manna said that the establishment of laws in Medina led to the formation of society and the establishment of rules in social matters. And the first step taken by Rasulullah SAW in building society was to bring brotherhood between the Muhajirin and the Ansar, whereby the Ansar people prioritized their brothers from among the Muhajirin over themselves.